A Three-layered Model of Nursing Based on Hospital Observation Data - Ohboshi, N.; Tanaka, T.; Kuwahara, N.; Ozaku, H. I.; Naya, F.; Kogure, K. (Methods of Information in Medicine, 2009)
Objectives: Our aim is to investigate causes of medical incidents and construct a knowledge base for preventing malpractice based on monitored data.Methods: To monitor nursing care, we developed an observing system of nursing activities with a ubiquitous sensor network and detecting errors in nursing care. This system is composed of a voice-recording device, mobile sensors and environmental setting type sensors. In cooperation with a hospital in western Japan, we have collected nursing activity data of nurses engaged at a combined ward, including ophthalmology, otolaryngology, and internal medicine for diabetes. After analyzing intravenous drip injection procedure (IVDI procedure) data, we introduce a three-layered model of nursing to understand nursing activities based on observed data. This model consists of three layers, 1) nursing care classification layer: Class, 2) nursing care step layer: Step, and 3) nursing care action layer: Action. This model is designed to take consistency with existing nursing care workflows.Results: We implemented a detection system and succeeded in comprehending the work-flow of IVDI procedure at the rate of over 95%. This system also can distinguish IVDI workflows performed in parallel by at least two or several nurses. We implemented a picture showing interface of IVDI workflows which can show each patient with a specific color and distinct nurses.Conclusions: Our system succeeded in verification of nursing care steps in IVDI procedure in ratios of more than 95%. Detection errors are due to the sensor system, so it is necessary to use or develop more precise devices.
Keywords: Nursing care; medical incident/accident; nursing workflow; ubiquitous sensor network